2004
DOI: 10.1097/01.aog.0000102704.29607.fc
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Examination and Dynamic Magnetic Resonance Imaging in Vaginal Vault Prolapse

Abstract: There is poor correlation between clinical and MRI findings when assessing vaginal apex prolapse. Magnetic resonance imaging allows the identification of other prolapsing compartments and may be a complementary diagnostic tool for the diagnosis of complex vaginal apex prolapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…Thus, a total of 509 studies were checked for eligibility, of which 432 studies could be excluded on the basis of title and abstract. The remaining 77 studies were read by paper, but only ten studies [24][25][26][27][28][29][30][31][32][33], published between 1993 and 2007, fulfilled the inclusion criteria. Sixty-one studies were excluded because they did not conform to our inclusion criteria: no report on a reference line used to stage the prolapse on dynamic MR imaging (n studies=1), no standardized method of gynecological prolapse staging (pre-or intraoperative; n studies=23), and no comparison of the dynamic MR imaging and gynecological prolapse staging (n studies = 7).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, a total of 509 studies were checked for eligibility, of which 432 studies could be excluded on the basis of title and abstract. The remaining 77 studies were read by paper, but only ten studies [24][25][26][27][28][29][30][31][32][33], published between 1993 and 2007, fulfilled the inclusion criteria. Sixty-one studies were excluded because they did not conform to our inclusion criteria: no report on a reference line used to stage the prolapse on dynamic MR imaging (n studies=1), no standardized method of gynecological prolapse staging (pre-or intraoperative; n studies=23), and no comparison of the dynamic MR imaging and gynecological prolapse staging (n studies = 7).…”
Section: Resultsmentioning
confidence: 99%
“…The bladder, and/or vagina, and/or rectum was/were opacified in three studies [25,29,33], whereas the other seven did not use opacification [24,[26][27][28][30][31][32], or even emptied the bladder [24,26,31]. Agildere et al [24] used an oral contrast agent (gadopentetatedimeglumine or gadopentetatedimeglumine plus polyethylene glycol).…”
Section: Resultsmentioning
confidence: 99%
“…Correlation of POP-Q stages with dynamic MR imaging has been studied before [6][7][8][9]. Until now, however, only one paper has compared the POP-Q centimeters and not the derivated POP-Q stages with measurements on dynamic MR imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Four previous studies have assessed the agreement of POP-Q measurements with the use of at least one reference line on dynamic MR imaging, but resulted in conflicting findings [6][7][8][9]. With respect to ultrasonography, only one study has compared perineal ultrasonography with POP-Q, and has found good correlation for the anterior and middle compartment and moderate correlation for the posterior compartment [10].…”
Section: Introductionmentioning
confidence: 99%
“…We propose that MRI evidence is objective and the clinical assessment was likely "under" staging maximal prolapse in the Singh study. Other studies reported a broad range in the agreement between MRI and clinical prolapse assessment, ranging from 41-85% [14,15]. Some studies reported discrepancies between MRI and POP-Q measurements as high as 3, 4, and 5cm for points Ba, C, and Bp, respectively [16].…”
Section: Discussionmentioning
confidence: 99%